2022
DOI: 10.1371/journal.pmed.1003860
|View full text |Cite
|
Sign up to set email alerts
|

Protection against discrimination in national dementia guideline recommendations: A systematic review

Abstract: Background National dementia guidelines provide recommendations about the most effective approaches to diagnosis and interventions. Guidelines can improve care, but some groups such as people with minority characteristics may be disadvantaged if recommended approaches are the same for everyone. It is not known if dementia guidelines address specific needs related to patient characteristics. The objectives of this review are to identify which countries have national guidelines for dementia and synthesise recomm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
9
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 25 publications
5
9
0
1
Order By: Relevance
“…Our ndings echo those of a 2022 systematic review investigating protection against discrimination in national guidelines for assessment, diagnosis and management of dementia (54). The authors highlighted that although most guidelines mentioned SDH and inequities, only a fraction included speci c recommendations to mitigate them (54).…”
Section: Discussionsupporting
confidence: 76%
“…Our ndings echo those of a 2022 systematic review investigating protection against discrimination in national guidelines for assessment, diagnosis and management of dementia (54). The authors highlighted that although most guidelines mentioned SDH and inequities, only a fraction included speci c recommendations to mitigate them (54).…”
Section: Discussionsupporting
confidence: 76%
“…In so doing, it supplements the aforementioned qualitative research ( Bamford et al, 2021 ; Wheatley et al, 2021 ) by revealing strategies that clinicians can apply to achieve holistic, person-centred dementia care. Our work also expands upon a prior analysis of dementia guidelines that specifically focused on intersectional factors, and like our study, found that most guidelines recognized the need to tailor dementia care to the needs of diverse persons ( James et al, 2022 ).…”
Section: Discussionsupporting
confidence: 71%
“…To foster the successful translation of the "new dementia" into effective public health initiatives, due attention must be paid to the uneven prevalence (and burden) of dementia risk factors across different populations, geographies and demographics. Evidence is starting to accumulate demonstrating that dementia risk factors play out differently for different people both nationally and at a global level (30,31).…”
Section: Study Hypothesis and Objectivesmentioning
confidence: 99%